FINANCIAL BEHAVIOR OF MUSLIM FAMILIES "ANALYSIS OF THEORY OF REASONED ACTION (TRA)" - Ningsih, Putri Apria; Rosmanidar, Elyanti; Nijal, Lasri (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 9 No 1 (2023): The 9th International Conference of Islamic Economics and Business (ICONIES 2023), 2023)
The issue in society is the continuous increase in divorce rates from year to year, and the main factor behind it is disharmony, which leads to prolonged conflicts that often end in divorce. However, divorce marks the beginning of the weakening of family unity or, conversely, the poor financial state of the family leads to divorce, ultimately resulting in the deterioration of the nation's prosperity. Therefore, it is important for the head of the family and the housewife to understand the financial attitudes of Muslim families according to the Theory of Reasoned Action (TRA). This study is qualitative and applies a descriptive method. Theory of Reasoned Action (TRA) is used as a guiding framework to analyze the collected data, which is then categorized and interpreted from a thematic analysis perspective. The research findings indicate that a Muslim's intention to behave is driven by worship, influenced by the values of monotheism (halal or permissible and good), moral ethics (faith, muhasabah or self-reflection, and self-auditing), and subjective norms (avoiding debt and self-reflection).